Structural and Functional Amygdala Abnormalities in Hemifacial Spasm - Xu, Hui; Guo, Chenguang; Li, Haining; Gao, Lin; Zhang, Ming; Wang, Yuan (Frontiers in Neurology, 2019)
Background and purpose: Hemifacial spasm (HFS) is a rare neuromuscular disorder characterized by unilateral, involuntary, and paroxysmal contractions of orofacial muscles. To elucidate the central neural mechanisms of HFS, we investigated brain grey matter and resting-state functional connectivity (rsFC) in HFS patients. Methods: Thirty patients with HFS and 30 age- and sex-matched healthy participants consented to the study. T1-weighted structural magnetic resonance imaging (MRI) and resting state BOLD images were collected in all participants. Cortical grey matter thickness was assessed, and subcortical volumetric analysis was performed. Seed-based rsFC analysis was performed on structurally abnormal regions in HFS patients. Post-hoc correlations with HFS severity and measures of mood (i.e. depression and anxiety) were performed to characterize rsFC alterations. Results: There were no significant differences in cortical thickness in HFS patients compared to healthy controls. Patients with HFS presented smaller right amygdala volume in contrast to healthy controls (q < 0.05, false-discovery rate corrected). We found that the right amygdala had increased rsFC with bilateral medial prefrontal cortex (mPFC), bilateral orbital frontal cortex (OFC), and left posterior insula (L postIns; voxelwise p<0.05, family-wise error corrected). Moreover, the connections of amygdala-postIns and amygdala-mPFC were positively related to HFS severity and anxiety, respectively. Conclusions: This is the first study to show structural and functional brain abnormalities in HFS. The volumetric and rsFC amygdala abnormalities were potentially driven by HFS, providing novel insights into HFS pathophysiology.